Characteristics of Canopy Conductance and Environmental Driving Mechanism in Three Monsoon Climate Regions of China - Wu, Rui-Qiao; Jia, Jian-Bo; Yan, Wen-De; Hu, Lei; Wang, Yi-Fan; Chen, Yu (Frontiers in Environmental Science, 2022)
Canopy conductance was an important index to measure the process of water exchange between canopy and atmosphere interface of forest ecosystem, as well as to judge the status of water use or the degree of drought stress, Therefore, the accurate estimation of forest canopy conductance was of great significance for the research of water use efficiency. In the past, Canopy conductance was measured on vegetation types in a single point region, but there were few studies on systematic comparison in different climate zones. Based on the data sets of EC flux and conventional meteorological elements from the eddy covariance (EC) flux observation station during 2003-2010 in three typical climate zones (Temperate continental monsoon climate zone, South subtropical monsoon climate zone and Mid-subtropical monsoon climate zone), Penman-Monteith model was used to calculate forest canopy conductance in different climate regions and analyze the dynamic changes of Canopy conductance in different time scales. At the same time, Combined with environmental factors including Temperature, Net radiation, Soil water content and Vapor pressure deficit to explore their driving ability on the canopy conductivity of forest ecosystem in different climate regions, and finally explored the mechanism driving the canopy conductivity of forest ecosystem under different climate, The results showed that: (1) The driving ability of environmental factors in different climate regions to the Canopy conductance was different, The contribution rate of Soil water content to the Canopy conductance in subtropical monsoon climate zone was the largest, It was 36.01%, the contribution rate of Vapor pressure deficit to the Canopy conductance in Mid-subtropical monsoon climate region was the largest, It was 29.4%, and the contribution rate of temperature to the Canopy conductance in temperate monsoon climate region was the largest, It was 28.14%; (2) Temperature was an important factor limiting and driving Canopy conductance, and there was a synergistic effect between water and temperature, which jointly drove the change of Canopy conductance; (3) Environmental factors in different climate regions had threshold for the synergistic driving effect of Canopy conductance. When the factors were within the appropriate threshold, the factors had a strong promoting effect on canopy conductance.